Logical use of antibiotics in canine skin disease. Issue 5 (22nd July 2013) - Craig, Mark
<x xml:space="preserve">Abstract</x> Antimicrobial resistance in companion animals is a growing problem, and veterinary practitioners must carefully select antimicrobial treatment. In this article, factors affecting antibiotic selection and common reasons for treatment failure in canine skin disease are discussed. A table of antibiotics licensed for sysemic administration in dogs with skin disease is included (2).